Increasing the efficiency of boiler plants with flue gas recirculation and deep heat recovery - Fialko, N.; Navrodska, R.; Shevchuk, S.; Sbrodova, G.; Stepanova, A. (Energy and Automation, 2023)
The thermal calculation results of a heating boiler plant with recirculation and heat recovery of flue gases are presented. The thermal efficiency of the complex heat recovery system use designed for heating the return heat-network water and blown air is investigated. Various options of flue gas selection for recirculation into the blowing air are considered, namely: after the boiler, after the water-heating heat recovery exchanger and after the air-heating heat recovery exchanger. The changes in the temperature of the exhaust gases regularities of the studied boiler plant various elements in the case of using the considered options for recirculated gas selection under conditions of changing their share in the air-gas mixture from 10 to 20 % and the relative heat load of the boiler from 30 to 100 % were established. Under these conditions, the levels of increase in efficiency in all elements of the boiler installation and the total efficiency with and without the proposed heat recovery system were determined. It is shown that the use of this system provides deep cooling of exhaust gases in the heat recovery process. The lower the temperature of the flue gas admixed in the options considered and the higher the share of gas recirculation, the lower the temperature of the exhaust gases for all elements of the boiler plant. The increase in the boiler plant efficiency due to the use of the proposed heat recovery system varies from 3 to 5 % in the case of a water-heating heat recovery exchanger and from 1 to 3 % in the case of an air-heating heat recovery exchanger, depending on the boiler load, the part of admixed gases and the options of their selection. The resulting increase in the boiler plant efficiency with a heat recovery and flue gas recirculation system is 1.4–4.7 %. Key words: gas-consuming boilers, deep cooling of flue gases, water and blowing air heating, and increased efficiency